Carcass Traits and Blood Biochemistry of Broiler Birds Fed Betaine Hydrochloride Supplemented Diets - Shubhnish; Sihag, Sajjan; Kumar, Sushil; Bai, Radha; Komal (Indian Journal of Animal Nutrition, 2025)
A study was conducted to assess the effect of different levels of betaine hydrochloride on the carcass characteristics and different blood biochemical parameters of broiler chicken. A total of 200 birds were allocated five different treatment groups of which T1 was taken as control while T2, T3, T4, and T5 were fed diet supplemented with 500, 1000, 1500 and 2000 mg/kg basal feed betaine hydrochloride, respectively. The percentage dressed, eviscerated and drawn carcass weight were significantly (P<0.05) higher in T5 group followed by T4 in contrast with T1, T2, and T3 groups. Birds of T5 group had the lowest abdominal fat and highest weight of lymphoid organs in comparison to control (T1). Both, T4 and T5 showed significantly higher breast and thigh percent weight, crude protein and moisture percentages and lowest ether extract, cholesterol and saturated fatty acid content in comparison to the other groups. Betaine supplementation resulted in increased haemoglobin and blood cell count while decreased heterophils count in comparison to control group. Birds in T5 group had higher total blood protein in comparison to the control. The groups supplemented with 2000 and 1500 mg betaine per kg feed had significantly (P<0.05) lower serum cholesterol, triglyceride and LDL values while significantly (P<0.05) higher HDL values in comparison to other groups. It was concluded that adding betaine in broiler diet improved the blood cell count, lymphoid organs, blood biochemical parameters with an increased yield of carcass with high protein, lower fat and lowered cholesterol content in comparison to the control group diet.